Artificial Intelligence Based Interactive Learning Media to Improve Science and Social Learning Outcomes of Fourth Grade Elementary School - Fu’adah, Maisya Nafidatul; Ratnaningrum, Ika (Journal for Lesson and Learning Studies, 2024)
The limited learning media used in IPAS learning makes students less motivated to learn and less optimal understanding of learning materials. These obstacles have an impact on the low learning outcomes of students. This research aims to create an interactive learning media based on artificial intelligence to improve the learning outcomes of grade IV elementary school. This type of research is development research (Research and Development). The development model used is the Borg & Gall development model. The subjects involved in this study consisted of a team of experts, classroom teachers, and grade IV students. Data collection techniques were obtained through observation, interviews, questionnaires, documentation, and tests. Techniques for analyzing data used initial data analysis techniques in the form of normality tests and final analysis techniques in the form of t tests and N-Gain tests. The results showed that the developed media was declared feasible and effective. Declared feasible based on validation from material experts obtained a score of 92.3% and media expert validation obtained a score of 96.4%, both in the very feasible category. It was declared effective based on the results of the pretest and post-test of students by conducting the N-Gain test obtained a score of 0.56 which showed that there was an increase in student learning outcomes in the moderate category. The conclusion of this study is that the artificial intelligence-based interactive learning media developed is feasible and effective use as a learning media to improve the learning outcomes of grade IV elementary school students.